Self-reported perceptions of factors influencing error reporting in one Nigerian hospital: a descriptive cross-sectional study - Afolalu, Olamide Olajumoke (Division of Nursing and Midwifery, 2018)
Background: Over the past decade the concern about patient safety due to the occurrence of medical errors has become a priority in healthcare. Medical errors occur from virtually all processes in the delivery of healthcare and while most have little risk for patient harm, some do result in injury, increased health care cost, lost income, decreased productivity, disability, morbidity and mortality. Under-reporting of medical errors is a global issue endangering patient safety and compromising health outcomes. Awareness and use of a hospital's error reporting system is an initial step towards improved reporting rates. Aim: The aim of the study was to describe doctors' and nurses' self-reported perceptions of factors influencing error reporting in a Nigerian hospital by survey questionnaire. Methods: This study employed a descriptive cross-sectional design to survey a random sample of 230 health professionals (n=90 doctors, n=130 nurses) working in all the units and departments of a Nigerian tertiary health institution. A theoretical model of a health information technology framework with implications for patient safety served as a guide for the literature review and interpretation of study findings. A 47-item self-administered survey questionnaire served as the data collection instrument. The questionnaire was developed following the review of available published literature and validated by four experts (n=2 doctors, 2 nurses), who determined the index of content validity. Inter-rater reliability of the instrument was subsequently measured by test-retest reliability of data from a pilot study of 30 raters (n=13 doctors, n=17 nurses). The validated questionnaire was used to determine doctors' and nurses' awareness and use of an error reporting system, frequency of reporting various types of errors, perceived barriers to error reporting and factors that facilitate an error reporting culture. Data collection took place for four weeks in February 2017. Data were analyzed in SPSS using descriptive and inferential statistics. Results: The median age of the respondents was 36 years (range of 25-59). The typical nurse respondent was female having a diploma in nursing and no Master's degree or PhD, in contrast to the doctors, most of whom were male and a few had a postgraduate qualification. The gender difference between the two groups was statistically significant (P<0.001). The majority of the respondents had 6-10 years of work experience and were in full-time employment and the difference in current work status (P=0.001) and years of work experience (P<0.001) between the two groups was statistically significant. Awareness of error reporting system: most respondents disagreed that the hospital had a system in place for reporting errors but more nurses (56/140, 40.0%) than doctors (16/90, 17.8%) were aware of such a system and the difference in responses between the two groups achieved statistical significance (X²(4, n=230) = 13.302, P<0.010); knew where and when to report errors (nurses 48.6%, n=68/140; doctors 20.0%, n=18/90) (X²(n=230) = 23.843, P<0.001); how to locate an incident form (nurses n=60/139, 43.2%; doctors n=28/89, 31.5%) (X²(4, n=228) = 9.842, P=0.043); and who to report an incident or error to (nurses n=72/140, 51.4%; doctors n=33/90, 36.7%) (X²(4, n=230) = 11.845, P=0.019). Results for type and frequency of errors reported and factors facilitating an error reporting culture did not achieve statistical significance. Perceptions of barriers to error reporting: lack of confidentiality (nurses n=62/140, 44.3%; doctors n=27/87, 31.0%) (X²(n=227) = 11.697, P=0.019). Most respondents were unsure if error reporting forms were easy to complete (nurses n=49/137, 35.8%; doctors n=26/88, 29.5%), (X²(4, n=225) = 9.926, P=0.042). Factors not perceived as barriers: positive feedback when reporting errors (nurses n=61/140, 43.6%; doctors n=24/90, 26.7%), (X²(n=230) = 10.939, P=0.026); reporting an error that did not cause harm (doctors n=40/90, 44.4%; nurses n=50/139, 36.0%), (X²(4, n=229) = 9.618, P=0.047); time involved in reporting (nurses n=76/138, 55.1%; doctors n=26/89, 29.2%), (X²(4, n=227) = 17.327); and learning from the error (doctors n=42/90, 46.7%; nurses n=40/138, 29.0%), (X²(4, n=228) = 20.777, P<0.001) Conclusion: Doctors and nurses were mostly unaware of the hospital's error reporting system which can be concluded to be an organizational factor. Respondents would be willing to report incidents if perceived barriers are removed. There is an urgent need for an effective error reporting system to be implemented in the local setting and for appropriate awareness training and educational interventions to improve doctors' and nurses' knowledge and use of medical error reporting. Relevance to clinical practice. Effective error reporting systems in the Nigerian healthcare sector that improve awareness and use of these systems should enhance a reporting culture and thereby improve patient safety.